Impact of COVID 19 on the provision of surgical services in Ontario, Canada: population-based analysis. Issue 1 (19th December 2020) - Gomez, D; Dossa, F; Sue-Chue-Lam, C; Wilton, A S; de Mestral, C; Urbach, D; Baxter, N
Abstract : In this population-based analysis, the rate of surgical procedures decreased during the COVID period with hospitals rapidly reducing ambulatory and in-patient elective procedures in response to government directives. However, the observed and unexpected large reduction in urgent surgical procedures highlights the need to prioritize access to care for patients with emergency surgical conditions as part of pandemic planning.